ФОРМУВАННЯ ВОКАЛЬНО-ХОРОВИХ НАВИЧОК ПІД ЧАС НАВЧАННЯ УЧНІВ СПІВУ (Педагогіка вищої та середньої школи, 2002)
The article deals with the questions of forming of vocal skills in the process of teaching pupils to sing: timbre qualities of voice,breathing, registries, attack of the sound, process of voice-making.The article is addressed to the pedagogical universities teachers on vocal music.